The Measurement of Language Knowledge as a Controversial Elaborative Linguistic Framework - Boughoulid, Mustapha; El Khatmi, Abdelkrim (International Journal of Language and Literary Studies, 2023)
This article is an attempt to determine the significance of vocabulary knowledge by describing its components and features on the basis of different existing models in such a way as to explore the language knowledge measurement criteria and find out the extent to which language knowledge is adequately measured. In fact, a plethora of research has been conducted on teaching and learning vocabulary, and testing vocabulary size. Though this linguistic element has been a controversial issue for so long, many scholars in the field of linguistics agreed upon the utility and the crucial role it has in relation to language teaching, learning, and testing. However, the investigation of the vocabulary knowledge takes into consideration three different aspects. The first aspect deals with vocabulary measurement, with the clarification of the differentiation between language knowledge in terms of its inference and language performance in terms of its observation. The second aspect examins the meaning of “word knowledge” by distinguishing between receptive and productive vocabulary knowledge. The third aspect deals with the qualitative aspect of the learners’ vocabulary knowledge in terms of understanding by identifying “breadth” and “depth”. This article also paves the way for the review of vocabulary size and the counting of family words on the basis of rigorous empirical studies in this field.